Using LЕGО-technologies for the correction of misinformation among young schoolchildren because of the mental development - Dorozhko , I.; Malykhina , O.; Turishcheva, L. (New Collegium, 2021)
Scientific work contains an analysis of psychological research on the problem of thinking of younger schoolchildren with mental retardation. The characteristics of the types of construction are presented, a theoretical substantiation of the effectiveness of the correction of thinking in younger schoolchildren in the process of LEGO technologies is given, the influence of classes with a designer on the development of thought processes in younger students with mental retardation is revealed. A correction program for working with younger schoolchildren with mental retardation has been tested.